Oral anticoagulant therapy for patients with new-onset atrial fibrillation following acute myocardial infarction: A narrative review - Yu, Shenglong; Li, Chenxi; Guo, Huizhuang (Frontiers in Cardiovascular Medicine, 2022)
Background: To evaluate the advantages and disadvantages of anticoagulant therapy and provide a piece of information on anti-thrombotic treatment strategies for patients with new-onset atrial fibrillation (NOAF) and acute myocardial infarction (AMI). Methods: Literature from PubMed and google scholar were screened until August 2022. Studies assessing oral anticoagulant treatments for NOAF in patients with AMI were evaluated for inclusion. Results: Three retrospective cohort studies were included. In the study performed by Madsen et al., patients with previously diagnosed AMI with or without NOAF were followed up for 5.8 years. About 38% of NOAF patients with anticoagulant therapies, which could reduce long-term mortality (adjusted hazard ratio (HR): 0.69; 95% confidence interval (CI): 0.47-1.00). Hofer et al. performed a single-center cohort study containing 1372 patients with AMI with an 8.6-year follow-up period. Dual anti-thrombotic therapy (DAT) did not show the effect on the survival in NOAF (adjusted HR: 0.97; 95% CI: 0.65-1.57), while triple antithrombotic therapy (TAT) could reduce long-term cardiovascular mortality (adjusted HR: 0.86; 95% CI: 0.45-0.92). Petersen et al. also did a cohort study with 1-year follow-up duration. It showed that anticoagulant therapies demonstrated positive results (HR: 0.78; 95% CI: 0.41-1.47). Conclusion: Recent studies have shown that anticoagulant therapy in AMI-NOAF patients has positive outcomes, especially oral anticoagulant (OAC) therapy. Further clinical trials could confirm these findings.